A meta-analysis of the line bisection task in children. Issue 1 (2nd January 2023) - Kaul, Danishta; Papadatou-Pastou, Marietta; Learmonth, Gemma
ABSTRACT: Meta-analyses have shown subtle, group-level asymmetries of spatial attention in adults favouring the left hemispace (pseudoneglect). However, no meta-analysis has synthesized data on children. We performed a random-effects meta-analysis of spatial biases in children aged ≤16 years. Databases (PsycINFO, Web of Science & Scopus) and pre-print servers (bioRxiv, medRxiv & PsyArXiv) were searched for studies involving typically developing children with a mean age of ≤16, who were tested using line bisection. Thirty-three datasets, from 31 studies, involving 2101 children, were included. No bias was identified overall, but there was a small leftward bias in a subgroup where all children were aged ≤16. Moderator analysis found symmetrical neglect, with right-handed actions resulting in right-biased bisections, and left-handed actions in left-biased bisections. Bisections were more leftward in studies with a higher percentage of boys relative to girls. Mean age, hand preference, and control group status did not moderate biases, and there was no difference between children aged ≤7 and ≥7 years, although the number of studies in each moderator analysis was small. There was no evidence of small study bias. We conclude that pseudoneglect may be present in children but is dependent on individual characteristics (sex) and/or task demands (hand used). Registration: Open Science Framework (https://osf.io/n68fz/ )